Menakar Keselarasan Hukum Nasional Terhadap Instrumen Internasional Dalam Pemenuhan Hak Access To Justice Masyarakat Adat - Yuldiana Zesa Azis; Marlyn Jane Alputila; Emiliana Bernadina Rahail; Nasri Wijaya; Ahmad Ali Muddin (Jurnal Restorative Justice, 2026)
Indigenous peoples in Indonesia systematically face normative and structural barriers that trigger the marginalization of their living spaces and the failure to fulfill their right to justice. This study aims to assess the degree of alignment between national regulations and international instruments, particularly the 2007 United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), regarding the right to access to justice for indigenous peoples, while mapping the normative barriers in domestic agrarian disputes. The research method employed is normative juridical, utilizing statutory, comparative, and conceptual approaches. The results demonstrate a sharp paradigm misalignment. UNDRIP promotes the recognition of inherent rights (sui generis) and the principle of Free, Prior, and Informed Consent (FPIC). Conversely, Indonesian positive law is characterized by state-centered positivism (positivisme etatis), which reduces customary land rights (hak ulayat) to state-granted rights through restrictive administrative prerequisites via Regional Regulations (Peraturan Daerah). At the judicial level, civil procedural law is highly formalistic-positivistic, elevating written evidence (Article 1867 of the Indonesian Civil Code) and thereby sidelining customary evidence based on oral traditions or natural boundaries. This condition is exacerbated by contemporary regulations, such as the Job Creation Law through the Land Bank institution and the New Criminal Code, which escalate conflicts and structural criminalization, as seen in Rempang Island and Nangahale. The prolonged delay in enacting the Indigenous Peoples Bill creates an absolute norm vacuum that perpetuates a pseudo formalistic-procedural justice. Therefore, a progressive reconstruction of legal policy is required through the accelerated enactment of the Indigenous Peoples Bill, the issuance of Supreme Court Regulations to equalize non-written evidence, and the integration of customary courts into the national judicial system to achieve substantive justice.